Голубая змейка: уральские сказки / П. П. Бажов - Бажов Павел Петрович (Серия "Внеклассное чтение", 2017)
Экземпляры: (20190910) / Инвентарный номер: 5236 / Цена: / Сис.шифр: 84(2=411.2)6-45 / Авт.знак: Б 16 / ББК: 84(2=411.2)6-45